Moon-Mung Phutai: The Process of Creating a Socio-Cultural Learning Space through Ethnic Textile Wisdom in Sakon Nakhon Basin, Thailand - Nontawan Saenprai; Charin mangkhang; Atchara Kerdtep (Journal of Green Learning, 2022)
The objectives of this article are to (1) study Moon-Mung Phutai in Sakon Nakhon basin in geographic, economic, social and cultural aspects; (2) study Moon-Mung of the ethnic textile wisdom of Phutai in Sakon Nakhon basin, Thailand, and (3) synthesize the pattern of the process of creating social-cultural space in terms of ethnic textile wisdom of Phutai in Sakon Nakhon basin, Thailand. This study uses the qualitative study method and participant observation. The results of the study found that (1) Moon-Mung Phutai in Sakon Nakhon basin area that is still preserved or inherited include belief in spirits and soul, language, food, weaving wisdom and fabric patterns, although their residence and occupation have changed (2) textile wisdom of Phutai ethnicity in Sakon Nakhon basin area is the ability of Phutai women to weave clothes for household use especially the Sarong which is called Tinto that has a specific aspect and an indigo-dyed three-quarter sleeve shirt, (3) the pattern of the process of creating a social and cultural space in terms of ethnic textile wisdom of Phutai in Sakon Nakhon basin is divided into 2 levels.